2020
DOI: 10.1371/journal.pone.0236481
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of RNA-dependent RNA polymerase 6 in tomatoes allows potato spindle tuber viroid to invade basal part but not apical part including pluripotent stem cells of shoot apical meristem

Abstract: RNA-dependent RNA polymerase 6 (RDR6) is one of the key factors in plant defense responses and suppresses virus or viroid invasion into shoot apical meristem (SAM) in Nicotiana benthamiana. To evaluate the role of Solanum lycopersicum (Sl) RDR6 upon viroid infection, SlRDR6-suppressed (SlRDR6i) 'Moneymaker' tomatoes were generated by RNA interference and inoculated with intermediate or lethal strain of potato spindle tuber viroid (PSTVd). Suppression of SlRDR6 did not change disease symptoms of both PSTVd stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Previous research reported that the accumulation of PSTVd was suppressed in transgenic SlRDR6 knockdown tomatoes, and the accumulation of PSTVd‐derived sRNAs in tomato plants correlated positively with that of PSTVd genomic RNA (Naoi et al, 2020 ). In our study, sRNA sequencing was used to confirm the accumulation of PSTVd sRNAs and identified specific RDR1‐amplified sRNAs in PSTVd‐infected EC and NtRDR1 plants.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research reported that the accumulation of PSTVd was suppressed in transgenic SlRDR6 knockdown tomatoes, and the accumulation of PSTVd‐derived sRNAs in tomato plants correlated positively with that of PSTVd genomic RNA (Naoi et al, 2020 ). In our study, sRNA sequencing was used to confirm the accumulation of PSTVd sRNAs and identified specific RDR1‐amplified sRNAs in PSTVd‐infected EC and NtRDR1 plants.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, the earliest signaling events in PTI responses include the influx of Ca 2+ , production of reactive oxygen species, and activation of mitogen-activated protein kinase (MAPK) cascades [ 49 ]. In PSTVd infection, induction of PTI responses was suggested from comprehensive transcriptome analyses in ‘Heinz 1706’ tomatoes, and MAPK3 was induced at both transcriptional and translational levels [ 50 ]; although the involvement of PTI in defense responses against viroids, including RNA silencing, has been suggested in a previous study [ 51 ], no studies have been conducted to prove that hypothesis. At 14 dpi, PSTVd accumulation was lower in F1 hybrids than in S. l. cerasiforme LA1286 but increased to an indistinguishable level at 5⁰ dilution at 21 dpi ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 5-fold dilution series from total RNA of 62.5 (in the case of wild relatives) or 31.25 ng (in the case of F1 hybrids) was prepared, spotted onto the Hybond-N membrane (GE Healthcare Life Sciences, Piscataway, NJ, USA), and crosslinked with UV irradiation. Hybridization was conducted with a digoxigenin-labeled cRNA probe for PSTVd [ 51 , 54 ]. Hybridized signals were visualized using ImageQuant LAS4000 (Fujifilm, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the accumulation of PSTVd in the early infection stage in a PSTVd-tomato combination was significantly lower in an RdRP6-knockdown "Moneymaker" tomato compared with that of the control plants; invasion into the apical meristem was, at most, up to the basal portion even in an RdRP6-knockdown tomato and did not reach the apical portion of the shoot apical meristem (SAM), unlike was reported in N. benthamiana. 133) Considering that the N. benthamiana derivative used was a natural loss-of-function variant of NbRdRP1, 134) these results suggested host factors other than RDRP6 (like RdRP1) may be involved in the protection of SAM and pluripotent stem cells from PSTVd invasion.…”
Section: Host Responses Against Viroid Infectionmentioning
confidence: 97%